HER2 (ERBB2) alterations in colorectal cancers - Nika Tavberidze; Wei Zhang (Elsevier, 2022)
Human epidermal growth factor receptor 2 / HER2 (erb-b2 receptor tyrosine kinase 2 / ERBB2) alterations are present in approximately 2-5% of metastatic colorectal cancers. Although, the full significance of the HER2 status in colorectal cancers is yet to be determined, the ongoing research revealed promising results by incorporating of HER2 targeted therapy in the management of the advanced disease. Based on these findings, the most recent National Comprehensive Cancer Network Colon cancer guidelines recommends HER2 testing in metastatic colorectal cancer, which can be conducted by immunohistochemistry, in situ hybridization, or next generation sequencing. While there are no universal criteria for interpreting HER2 alterations, many specialists refer to HERACLES and MyPathway basket clinical trial criteria for the determination of HER2 status.